PURE AND APPLIED SCIENCE FOR VISION 2030 - Kigo, Josephat K. (Kabarak university, 2013)
Pure and applied science, in its broadest sense, means much more than simply being able to read, understand and write about pure and applied science and technology, however important these are. This also includes the ability to apply scientific and technological concepts and process skills to the life, work and culture of one's own society. This paper aims at simplifying the concepts pure and applied science for utility by the population towards technological development benefits and challenges. The understanding of the concepts will lead to policies that reinforce investment and motivation in enrolment in pure science courses at various levels of Education. Training in pure and applied sciences gives a strong foundation to enhance literacy in technological advancement. This will enhance developing of career and skills relevant to the attainment of Kenya Vision, 2030. A literate population will manage its destiny better and harness resources at their disposal in a highly technological world. Understanding of basic scientific principles and laws will lead to respecting simple protocol processes e.g. curing in construction, basic health principles, etc. The population equipped with knowledge of pure and applied science will be sensitive to cause of accidents, wastage, efficiency, and conflicts with nature, technology and self. In bringing out the differences between pure and applied science in research and development, a few of the scientist and their discoveries will be discussed. A discussion on applied science and Technology to eliminate confusion of concepts is worth venturing into.  Key words: Pure and applied science, Utility, Enrolment, Literacy, Scientific principle, Technology